Design of A Web-Based Teacher Performance Evaluation System at Vocational School - Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Theno, Ignatius Rudi; Paat, Wensi R. L.; Maringka, Riviva W; Dondokambey, Rainier N (International Journal of Information Technology and Education, 2023)
This research is about the web-based evaluation of teacher performance at SMK Negeri Tabukan Utara. The method used in this research is the research and development (R&D) method. The research and development method is the steps in implementing research and development strategies that are carried out to produce certain products and to test the effectiveness of these products. The software development model used is a rational unified process (RUP). The RUP development model was chosen because this model can be adaptive and adapted to the needs of the information system development process. The RUP model is divided into four stages, namely: inception, elaboration, construction, and transition stages.